The Effect of Barotropic and Baroclinic Tides on Three‐Dimensional Coastal Dispersion. Issue 20 (16th October 2018) - Suanda, Sutara H.; Feddersen, Falk; Spydell, Matthew S.; Kumar, Nirnimesh
Abstract: The effects of barotropic and baroclinic tides on three‐dimensional (3‐D) coastal dispersion are examined with realistic, 200‐m horizontal resolution simulations of the Central Californian continental shelf during upwelling. Over multiple tidal cycles, the horizontal relative dispersion and vertical dispersion of 3‐D drifters are similar between simulations with no tides and with barotropic tides. In contrast, baroclinic tides, which dissipate across the shelf and induce vertical mixing, result in a factor of 2–3 times larger horizontal and vertical dispersion. The increase in horizontal dispersion with vertical mixing is qualitatively consistent with weak‐mixing shear dispersion. Without shear dispersion, horizontal dispersion of surface‐trapped (2‐D) drifters was similar in all simulations. However, 2‐D drifter trajectory differences relative to no tide simulations are 3–4 times larger with baroclinic tides than barotropic tides alone. These results demonstrate the need to include baroclinic tides and 3‐D tracking for coastal passive tracer dispersion. Plain Language Summary: Understanding the dispersal of material in the coastal ocean is relevant to pollutant dilution, marine ecosystem sustainability, and search‐and‐rescue operations. Although numerical circulation models are commonly used to predict material dispersal, these models often do not include tides. Here the tidal effect on material dispersal is compared with numerical drifters released in a realistic model without tides, with surface tides (the rise and fall of sea level), and with internal tides (the rise and fall of interior density layers). Surface tides contribute little additional dispersal in the model region, while internal tides induce 2–3 times larger horizontal and about 2 times larger vertical dispersal in comparison to models without tides. In addition, after 48 hr surface drifter trajectory differences between models with and without internal tides are 8 km. Therefore, internal tides need to be considered in models used to plan oil‐spill response or search‐and‐rescue operations. Key Points: Compared to realistic models without tides, baroclinic tides induce 2‐3 times larger horizontal and vertical dispersion Three‐dimensional drifter tracking is important for passive tracer dispersion